Global White Matter Hypoperfusion on CT Predicts Larger Infarcts and Hemorrhagic Transformation after Acute Ischemia. (18th January 2016) - Bivard, Andrew; Cheng, Xin; Lin, Long‐Ting; Levi, Christopher; Spratt, Neil; Kleinig, Tim; O'Brien, Billy; Butcher, Kenneth; Lou, Min; Zhang, Jing‐Fen; Sylaja, PN; Cao, Wen‐Jie; et al.
Summary: Introduction: Presence of white matter hyperintensity (WMH) on MRI is a marker of cerebral small vessel disease and is associated with increased small vessel stroke and increased risk of hemorrhagic transformation (HT) after thrombolysis. Aim: We sought to determine whether white matter hypoperfusion (WMHP) on perfusion CT (CTP) was related to WMH, and if WMHP predisposed to acute lacunar stroke subtype and HT after thrombolysis. Methods: Acute ischemic stroke patients within 12 h of symptom onset at 2 centers were prospectively recruited between 2011 and 2013 for the International Stroke Perfusion Imaging Registry. Participants routinely underwent baseline CT imaging, including CTP, and follow‐up imaging with MRI at 24 h. Results: Of 229 ischemic stroke patients, 108 were Caucasians and 121 Chinese. In the contralateral white matter, patients with acute lacunar stroke had lower cerebral blood flow (CBF) and cerebral blood volume (CBV), compared to those with other stroke subtypes ( P = 0.041). There were 46 patients with HT, and WMHP was associated with increased risk of HT ( R 2 = 0.417, P = 0.002). Compared to previously reported predictors of HT, WMHP performed better than infarct core volume ( R 2 = 0.341, P = 0.034), very low CBV volume ( R 2 = 0.249, P = 0.026), and severely delayed perfusion (Tmax>14 second R 2 = 0.372, P = 0.011). Patients with WMHP also had larger acute infarcts and increased infarct growth compared to those without WMHP (mean 28 mL vs. 13 mL P < 0.001). Conclusion: White matter hypoperfusion remote to the acutely ischemic region on CTP is a marker of small vessel disease and was associated with increased HT, larger acute infarct cores, and greater infarct growth.